Understanding large‐scale, complex, human–environmental processes: a framework for social–ecological observatories. (7th May 2018) - Bourgeron, Patrick; Kliskey, Andrew; Alessa, Lilian; Loescher, Henry; Krauze, Kinga; Virapongse, Arika; Griffith, David L
Abstract : There is a growing consensus that transdisciplinary environmental networks are required to generate knowledge of the dynamics of coupled human–natural systems (CHANs) and to assess societal and policy consequences of complex environmental issues. Few of the existing large environmental observatory networks collect much, if any, data on the CHANs coupling mechanisms, reaffirming the need to develop observing approaches and structures that address the interoperability of the diverse data being obtained from these systems. We review the characteristics of existing environmental observatories and similar initiatives used to monitor CHANs, and identify opportunities for interoperability among them. From a synthesis of the characteristics of environmental networks representing a wide spectrum of research approaches and applications, a conceptual framework of a typical Social–Ecological Observatory (SEO) is presented to support long‐term, multi‐scaled CHANs observations through a common set of principles for organizing the observatories. Finally, we identify three areas of emphasis where progress is needed to support the use and application of SEOs.